The Influence of Socio Demographic Factors and Human Resource Capacity on The Empowerment of Sasirangan Fabric Craftsmen in Sasirangan Village, Banjarmasin City - Rusnawati Rusnawati; Muhammad Alif; Muhammad Riduansyah Syafari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of socio-demographic factors and human resource capacity on the empowerment of Sasirangan craftsmen in Sasirangan Village, Banjarmasin. A quantitative approach with a survey method was employed, involving 31 craftsmen as respondents. Data were analyzed using multiple linear regression after conducting classical assumption tests. The results showed that partially, socio-demographic variables (gender, age, education, income, and length of work) did not have a significant effect on empowerment (p = 0.447 > 0.05). In contrast, human resource capacity (knowledge, leadership, collaboration networks, community appreciation, and information access) had a positive and significant effect on empowerment (p = 0.000 < 0.05) with a regression coefficient of 0.563. Simultaneously, both variables significantly influenced empowerment based on the F-test (p = 0.000 < 0.05). The R Square value of 0.471 indicates that 47.1% of the variation in empowerment is explained by both variables. These findings indicate that craftsmen's empowerment is not determined solely by individual demographic characteristics but is rather influenced by human resource capacity built through training, mentoring, access to information, and institutional networks. Therefore, empowerment programs should prioritize comprehensive human resource capacity strengthening